Methodological Proposal to Conduct a Conglomerate Self-Assessment Process in University Careers - Morera-Castro, María; Azofeifa-Mora, Christian; Gómez-Barrantes, Viviana; Azofeifa-Lizano, Ana; Rojas-Valverde, Daniel (Revista Electrónica Educare, 2019)
The purpose of this article was to systematize the methodological experience lived in the conglomerate process of self-evaluation of university graduate careers, which are in different stages of evaluation and have two executing units. This proposal includes the phases and stages that have all the methodological details, including design of an action plan, permanent collective meetings for the systematization and decision-making, and design of tools to standardize the accreditation process by conglomerate mainly. As a result of this methodological application, the form of work established by the commission is concluded as a successful strategy; it allowed a group cohesion, sense of belonging, and appropriation of the process. This article can be used as a document to guide the academic activities of self-evaluation and improvement in careers that have a high degree of affinity between them, either from their object of study or educational process, in order to be accredited.